Image, video and 3D data registration : medical, satellite and video processing applications with quality metrics /: medical, satellite and video processing applications with quality metrics. (2015) - Argyriou, Vasileios; Martinez Del Rincon, Jesus; Villarini, Barbara; Roche, Alexis
No abstract available